Di Tengah Revolusi Kemerdekaan: Restorasi Kesultanan Jambi dan Persatuan Negara Republik Indonesia - Muzakir, Ali (Nazharat: Jurnal Kebudayaan, 2024)
This research aims to analyze the dynamics of social and political history during the independence revolution in Jambi. This research is a historical analysis of the interaction between the Jambi people in the region and the central government as recorded in various historical references. The flow of history is described chronologically. Therefore, local historical references are also highly appreciated because they have recorded events in more detail. This paper shows that the history of events in Indonesia's regions is an integral and decisive part of the struggle through which the country gained its independence. The case of Kertapati who wanted to restore the sultanate's aspirations and political dynamics during the revolution.